2009
DOI: 10.1051/apido/2008065
|View full text |Cite
|
Sign up to set email alerts
|

Nosema ceranaeinfects honey bees (Apis mellifera) and contaminates honey in Australia

Abstract: -Polymerase chain reaction (PCR), restriction fragment length polymorphism (RFLP) analysis and microscopy were used to test 307 adult bee and 37 honey samples collected in Australia for the presence of two microsporidia, Nosema ceranae and Nosema apis. N. ceranae was detected in samples from 4 states (Queensland, New South Wales, Victoria and South Australia) and was most commonly found in samples from Queensland where 28 (33.7%) of 83 samples were positive. New South Wales had the second highest prevalence wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 16 publications
3
93
0
1
Order By: Relevance
“…N. ceranae was confirmed in many European countries (Paxton, Klee, Korpela, & Fries, 2007) including Canada and USA (Williams, Shafer, Rogers, Shutler, & Stewart, 2008). N. ceranae infects A. mellifera populations elsewhere in the world (Chen, Evans, Smith, & Pettis, 2008;Giersch, Berg, Galea, & Hornitzky, 2009;Higes, Martin, & Meana, 2006, Huang, Jiang, Chen, & Wang, 2007Invernizzi et al, 2009. Nosema spores which are present in faeces but can also be found in pollen, infect adult bees upon ingestion (Higes et al, 2008).…”
Section: ) European Foulbroodmentioning
confidence: 96%
“…N. ceranae was confirmed in many European countries (Paxton, Klee, Korpela, & Fries, 2007) including Canada and USA (Williams, Shafer, Rogers, Shutler, & Stewart, 2008). N. ceranae infects A. mellifera populations elsewhere in the world (Chen, Evans, Smith, & Pettis, 2008;Giersch, Berg, Galea, & Hornitzky, 2009;Higes, Martin, & Meana, 2006, Huang, Jiang, Chen, & Wang, 2007Invernizzi et al, 2009. Nosema spores which are present in faeces but can also be found in pollen, infect adult bees upon ingestion (Higes et al, 2008).…”
Section: ) European Foulbroodmentioning
confidence: 96%
“…Detection of Nosema apis, N. ceranae, Ascosphaera apis and Paenibacillus larvae in samples of bee products has been reported (Cox-Foster et al 2007, Higes et al 2008, Giersch et al 2009), but few studies have reported the detection limits.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some negligent hygienic practices by beekeepers, such as reuse of apiculture materials (Van der Zee 2010), exchange of combs containing the remains of diseased broods (OIE 2014), and reuse of contaminated wax (Malone and Gatehouse 1998;OIE 2014), among other practices (Higes et al 2008;Aronstein and Murray 2010), are indicated as important routes for dissemination of these pathological agents (Hale and Menapace 1980;Higes et al 2008;Giersch et al 2009). For this reason, research has been carried out to develop methods to detect pathogens in bee products, mainly involving the use of polymerase chain reaction (PCR) (de Graaf et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2008) collected samples of honey bees between the years 1995 to 2007 and found the pathogen in 12 states in the USA; Liu et al (2008) reported it in China, while other reports over the years include Canada (Williams et al 2008a); Greece (Bacandritsos et al 2010); Thailand (Chaimanee et al 2010); different prefectures in Japan (Yoshiyama and Kimura 2011); several Balkan countries (Stevanovic et al 2011); and Turkey (Whitaker et al 2011). Moreover, Klee et al (2007) reported that N. ceranae is a disease of global proportions detected in many parts of the world, including Europe, Africa, Asia, America and Oceania (Higes et al 2006, Calderón et al 2008, Giersch et al 2009b , Chen and Huang 2010. In South America, studies have confirmed the presence of N. ceranae in Brazil (Texeira et al 2013), Uruguay (Invernizzi et al 2009), Argentina (Plischuk et al 2009, Medici et al 2012 and Chile (Martínez et al 2012, Rodríguez et al 2012.…”
Section: Discovery and Geographical Distributionmentioning
confidence: 99%